Respuestas
Respuesta dada por:
2
Hola,
Lo puedes hacer por el metodo de la suma:
![\left \{ {{x+y=1250} \atop {x-y=750}} \right. \left \{ {{x+y=1250} \atop {x-y=750}} \right.](https://tex.z-dn.net/?f=+%5Cleft+%5C%7B+%7B%7Bx%2By%3D1250%7D+%5Catop+%7Bx-y%3D750%7D%7D+%5Cright.+)
![2x=1250+750 2x=1250+750](https://tex.z-dn.net/?f=2x%3D1250%2B750)
![x= \frac{2000}{2} x= \frac{2000}{2}](https://tex.z-dn.net/?f=x%3D+%5Cfrac%7B2000%7D%7B2%7D+)
![x=1000 x=1000](https://tex.z-dn.net/?f=x%3D1000)
Reemplazas x en la ecuacion 1 y hallas y
![(1000)+y=1250 (1000)+y=1250](https://tex.z-dn.net/?f=%281000%29%2By%3D1250)
![y=1250-1000 y=1250-1000](https://tex.z-dn.net/?f=y%3D1250-1000)
![y=250 y=250](https://tex.z-dn.net/?f=y%3D250+)
Lo puedes hacer por el metodo de la suma:
Reemplazas x en la ecuacion 1 y hallas y
rariza69:
Gracia
Preguntas similares
hace 6 años
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años